A novel soil manganese mechanism drives plant species loss with increased nitrogen deposition in a temperate steppe. Issue 1 (29th January 2016) - Tian, Qiuying; Liu, Nana; Bai, Wenming; Li, Linghao; Chen, Jiquan; Reich, Peter B.; Yu, Qiang; Guo, Dali; Smith, Melinda D.; Knapp, Alan K.; Cheng, Weixin; Lu, Peng; et al.
Abstract: Loss of plant diversity with increased anthropogenic nitrogen (N) deposition in grasslands has occurred globally. In most cases, competitive exclusion driven by preemption of light or space is invoked as a key mechanism. Here, we provide evidence from a 9‐yr N‐addition experiment for an alternative mechanism: differential sensitivity of forbs and grasses to increased soil manganese (Mn) levels. In Inner Mongolia steppes, increasing the N supply shifted plant community composition from grass–forb codominance (primarily Stipa krylovii and Artemisia frigida, respectively) to exclusive dominance by grass, with associated declines in overall species richness. Reduced abundance of forbs was linked to soil acidification that increased mobilization of soil Mn, with a 10‐fold greater accumulation of Mn in forbs than in grasses. The enhanced accumulation of Mn in forbs was correlated with reduced photosynthetic rates and growth, and is consistent with the loss of forb species. Differential accumulation of Mn between forbs and grasses can be linked to fundamental differences between dicots and monocots in the biochemical pathways regulating metal transport. These findings provide a mechanistic explanation for N‐induced species loss in temperate grasslands by linking metal mobilization in soil to differential metal acquisition and impacts on key functional groups in these ecosystems.